THE ECONOMIC OF SUICIDE: AN EMPIRICAL STUDY OF WORLD FORTY COUNTRIES WITH THE HIGHEST SUICIDE RATE - Alfina Hidayati (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2017)
Though sociologists and economists have developed and tested numerous theories about suicide, still very many professionals especially in Indonesia remain unaware about the economics of suicide phenomenon. We derive an economic theory of suicide and test its implications using: (1) data by suicide number as, income (GNI), population over the age of sixty-five, population of density, and unemployment rate as in forty countries in the world with the highest suicide rate; (2) a panel data in 2000 until 2015; (3) multiple regression analysis; (4) EViews 9 software. Most of our predictions are verified. In particular, the result shows that population over the age of sixty-five, income, and population density significantly affect suicide number, while unemployment rate does not. The implied effect of income on suicide number is positive, as is the positive relationship between population density to suicide number. While population over the age of sixty-five give a negative impact to suicide number.Keywords: Suicide, Suicide number, Income, Population over the age of sixtyfive, Population of density, and Unemployment rate